Paul Apostle of liberty - Longenecker, Richard Norman, 1930- (Grand Rapids, MI Baker, 1964)
Includes bibliographical references and indexes.
Keywords: Paul, the apostle, saint -- biographies; Paul, the apostle, saint -- theology